SISTEM PENDETEKSI KESALAHAN PADA KALIMAT BAHASA INGGRIS - Ping Lak, Richard Lung; Sholeh, Muhammad; Hamzah, Amir (Jurnal Script, 2013)
ABSTRACT In learning English there is a grammar that is used as the standard language used to know it is correct or not . Standards are used commonly called grammar . These days a lot of the applications that have sprung translator said , both online and offline . However , there is still a structural deficiency in these applications so confusing society in terms of learning English . In this application used a bottom-up method that works to detect one by one word in the sentence to be detected . Therefore, the method used is very useful in the detection process . Applications are made to make the process of detecting errors in the English language structurally sentence . In addition to detection , there is a feature grammar tutorials and Indonesia to English dictionary to support English language learning , ordinary people can also use this application because the application view is very simple and easy to use . Therefore , with this application, it is expected that people can learn or know the structural errors in English sentences and also can improve the process of learning English effectively and efficiently. Keywords: detection, english language, grammar.